Arbitragem no investimento estrangeiro: segurança jurídica - Cracken, Roberto Nussinkis Mac (2014)
Arbitration is a dispute resolution method resulting from the will of the parties with full civil capability that rather settle their conflict by submitting it to another private individual, elected by them, so they can avoid the bureaucracy established by the State courts. Its creation, according to the doctrine, stems from ancient times, including its application in ancient Rome. This work will address all developments related to arbitration, more specifically in a national dimension with regards to the increasing use of arbitration. It aims at drawing new investments with the appropriate legal certainty, as well as at its materialization through a contractual instrument. It will also be analyzed the extent of the arbitration effects and its binding manner, the arbitration procedure established by ordinary legislation, and its application as an "alternative means" of dispute resolution in international relations. In brief, the main purpose of this thesis is to demonstrate the advantages that arbitration may bring, which can be translated into effective benefits that will be specifically analyzed in this study, in a way that may demonstrate a higher level of legal certainty and, consequently, a greater and better possibility of foreign investments